(untitled) (Annals of Medical Research, 2021)
Aim: To evaluate the effects of local anesthetic use on non-contact tonometry (NCT) measurement results and patient comfort and to compare the intraocular pressure (IOP) readings obtained with Shin Nippon NCT-10 tonometer and Goldmann applanation tonometry (GAT).Material and Methods: 31 healthy participants were included in this study. Central corneal thicknesses (CCT) were measured. All IOP measurements were performed in the same order as NCT without anesthesia, NCT with local anesthesia and GAT with anesthesia, respectively. After the measurements, participants were asked to rate the pain felt during IOP measurements. The range was from 0 to 10; 0= very painful/reading impossible, 10=no sensation at all/reading very easily obtained. Less pain was evaluated as more comfort.Results: NCT (p=0.007) and NCT-local (P=0.001) measurements overestimated IOP compared to GAT. IOP measured in NCT and NCT-local groups were similar (p=1.00). Mean patient comfort score was higher in GAT group than NCT group (p=0.006). Compared with NCT-local group, mean patient comfort score was lower in NCT group (P=0.033). Mean patient comfort scores were similar in GAT and in NCT-local groups (p=0.615). A positive but statistically insignificant correlation was found among NCT (r=0.201, p=0.277), NCT-local (r=0.259, p=0.160), GAT (r=0.272, p=0.139) measurements and CCT. Conclusion: Compared to NCT, IOP measurement with GAT is more comfortable. Performing NCT measurements with local anesthesia increases the patient comfort without changing the IOP values. The measurements with Shin Nippon NCT-10 with or without local anesthesia overestimated IOP compared to the GAT and cannot be used interchangeably with the GAT.